Means-End chain approach explains motivations to consume insect-based foods: the case of Cricket-Scones in Kenya - Pambo, K.O.; Okello, J.J.; Mbeche, R.M.; Kinyuru, J.N. (Springer, 2018)
Edible insects are being promoted as a sustainable and inexpensive alternative of enhancing nutrition because they can provide proteins, good fats such as the polyunsaturated fatty acids (PUFAs), calcium, vitamins, and energy. But little is known regarding what drives individuals to consume insect-based foods. The current study seeks to explain the effect of personal values on “cricket-scones” (used interchangeably with cricket-based scones) consumption in a developing country’s context. Employing laddering interviews and the means-end chain analysis, the relationship between “attributes” of cricket-scones, “consequences” of consuming them (outcomes), and personal “values” driving consumers’ decision-making process were systematically mapped to generate mental models related to consuming insect-based products. The personal values identified in this study cluster under the headings of “happy life”, “(food) security”, and “long life”. Amongst these, the main evidence (ladders) pointed to the desire to have a “happy life” and a “long life” that arise from improved family nutrition and financial position. Moderating these results by gender revealed higher involvement for males. The findings suggest that cricket-scones enhance the goals of achieving core personal values. Campaigns aiming to promote edible insects should therefore be premised on local food policies designed along the identified consumer-motivations. Other than the common nutritional and environment-friendly themes that have been used to promote edible insects; “happy life”, “(food) security”, and “healthy life” themes emerged as the central messages for the development of insect-based foods’ campaign strategies. Other empirical information in this study also have insightful policy implications.